Detailed protocol for the lifestyle intervention in the BeWEL randomised controlled trial of weight loss in adults who have had a colorectal adenoma. Issue 3 (25th May 2012) - Caswell, Stephen; Craigie, Angela M; Wardle, Jane; Stead, Martine; Anderson, Annie
Abstract : Introduction: The BeWEL study is aimed at assessing the impact of a personalised lifestyle programme on body weight in people at risk of developing colorectal adenomas. The study is a two-arm multicentre randomised controlled trial comparing the BeWEL lifestyle programme against usual care. Over 12 months, 316 people who have had a colorectal adenoma removed through the national screening programme will be randomised to provide 80% power to detect a weight loss (primary outcome) of 7% over 12 months. Methods: The 12-month intervention will be delivered by lifestyle counsellors via three face-to-face visits followed by nine monthly telephone support calls. Consultant endorsement for the study will be stressed. An individualised caloric prescription based on estimates for weight maintenance −600 kcal will be calculated. Motivational interviewing techniques will be used to identify personal motivations for weight change and ways to improve perceived self-efficacy. The programme will utilise personalised diet and physical activity data from baseline measures to set behavioural goals. A range of behavioural strategies will be employed to support lifestyle change including goal setting, identifying specific implementation intentions, self-monitoring and feedback. Emphasis will be placed on self-monitoring body weight, and weighing scales will be provided. Programme acceptability will be explored postintervention with indepth interviews. Compliance and impact will be assessed by baseline and follow-up measures of diet by self-report, activity by accelerometry and anthropometry. Ethics and dissemination: Ethical approval has been obtained from the Tayside Committee on Medical Research Ethics. Dissemination of results will focus on publications in peer-reviewed journals, presentations at national/international cancer meetings and NHS groups. In addition, the work will be communicated to the public through forums such at The Scottish Cancer Prevention Network (http://www.cancerpreventionscotland.co.uk/ ). The trial is registered with Current Controlled Trials (International Standard Randomised Controlled Trials No: ISRCTN53033856 ).